Understanding hybrid journalism: the emergence of the jinfluencer phenomenon - Ghergut-Babii, Alexandra-Niculina; Poleac, Gabriela (Technium Social Sciences Journal, 2025)
This theoretical study explores the emerging phenomena of “jinfluencers” (influencer journalists) and their disruptive impact on the contemporary journalistic scene. The research examines how these digital-native communicators are using social media platforms to spread news and information, offering a substitute for well-established traditional media channels, with a focus on Romania’s changing media landscape. Through the development of distinctive personal brands that appeal to particular audiences and their frequent independence, our research addresses the ways in which jinfluencers have established themselves in Romani’s media landscape. Using a theoretical framework, the paper investigates the fundamental elements driving this trend, such as the changing nature of conventional news outlets, the democratisation of information via digital platforms, and the changing public views of influencer relatability and trust.